Phytochemical screening, total phenolic content, antioxidant and cytotoxic activity of chromolaena laevigata on human tumor cell lines - Herrera-Calderon, Oscar (2017)
Aims: Cancer is the first cause of death in the Peruvian population; searching alternative treatments of medicinal plants constitute a promissory field to find new anticancer drugs. The main objective in this study was to evaluate the phytochemical screening, total phenolic content, antioxidant and cytotoxic activity of ethanol extract of Chromolaena laevigata (C. laevigata) on human tumor cell lines. Study Design: The fresh leaves of C. laevigata were soaked with ethanol followed by phytochemical screening using standard methods. Place and Duration of Study: Laboratory of Applied Chemistry, Faculty of Pharmacy and Biochemistry, Universidad Nacional San Luis Gonzaga de Ica, Ica, Peru; Laboratory “Abraham Vaisberg Wolach”, Universidad Peruana Cayetano Heredia, Lima, Peru. Methodology: Phytochemical screening was assessed by using chemical reactives. Total phenolic content (TPC) was developed using Folin Ciocalteu reactive and the antioxidant activity was determined against DPPH and ABTS radicals by spectrophotometry. The cytotoxic activity was determined on human tumor cell lines followed as: MCF-7, H-460, HT-29, M-14, K-562 and DU-145. Results: Phytochemical study confirmed flavonoids and phenolic compounds in ethanol extract. TPC resulted 45.21 ± 3.5 mg of gallic acid equivalent/g of dried extract. The highest antioxidant extract for DPPH and ABTS radical scavenging tests were IC50 = 11.66 ± 1.0 μg/mL, IC50= 12.45 ± 0.50 μg/mL respectively. Ethanolic extracts (μg/mL) showed a low cytotoxicity on human tumor cell lines (CI50 > 20 μg/mL) for DU-145, HT-29, MCF-7 and M-14. Whereas, for H-460, and K562 tumor cell lines showed high cytotoxicity. Conclusion: In our findings, C. laevigata demonstrated a high antioxidant and total phenolic content. The ethanol extract exhibited better cytotoxic effect compared with 5-FU. Hence, This medicinal plant could be effective to prevent chronical diseases as cancer and oxidative stress disorders.